(3jGbhJI GdZjGUI GdLGeYI deYGfi GdNdGUI GdfGaYIs - (3CHh YHO Gddg eMeO Hf jMji Hf CMeO Hf MfT GdjeGfj GdRjOj,J (B717 (3g` s
(3ChdgG (B:s
(3bGd SjOfG eMeO Hf jMji hEPG CQOfG GdcdGe ai ePGcQI gPG GdcJGH JcdefG ai SHYI aUhd GdChd s
(3BNQgG (B:s
(3HNdGa GdaQhY aEf WQjbgG djS HeQcH ai Ybhdge Hd gh eHfi Ydi GdcJGH hGdSfI Je GdcJGH HMeO Gddg JYGdi hefg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HNW eLhO HYVgG cJH HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3hgh cJGH ai GdYdhe GdTQYjI eQJH Ydi SHYI aUhd s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdESdGejs